Cardiovascular Malformations in CHARGE Syndrome with DiGeorge Phenotype: Two Case Reports. (10th November 2016) - Yasuda, Kazushi; Morihana, Eiji; Fusazaki, Naoki; Ishikawa, Shiro
Abstract : Both CHARGE syndrome and DiGeorge anomaly are frequently accompanied by cardiovascular malformations. Some specific cardiovascular malformations such as interrupted aortic arch type B and truncus arteriosus are frequently associated with 22q11.2 deletion syndrome, while conotruncal defects and atrioventricular septal defects are overrepresented in patients with CHARGE syndrome. CHD7 gene mutation is identified in approximately two-thirds of patients with CHARGE syndrome, and chromosomal microdeletion at 22q11.2 is found in more than 95% of patients with 22q11.2 deletion syndrome. CHARGE syndrome is occasionally accompanied by DiGeorge phenotype. We report two patients with dysmorphic features of both CHARGE syndrome and 22q11.2 deletion syndrome. Although both of the two cases did not have 22q11.2 deletion, they had typical dysmorphic features of 22q11.2 deletion syndrome including cardiovascular malformations such as interrupted aortic arch type B. They also had characteristic features of CHARGE syndrome including ear malformation, genital hypoplasia, limb malformation, and endocrinological disorders. CHD7 gene mutation was confirmed in one of the two cases. When a patient with cardiovascular malformations frequently associated with 22q11.2 deletion syndrome does not have 22q11.2 deletion, we suggest that associated malformations characteristic of CHARGE syndrome should be searched for.